2007
DOI: 10.1152/ajplung.00338.2006
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone prevents transport inhibition by hypoxia in rat lung and alveolar epithelial cells by stimulating activity and expression of Na+-K+-ATPase and epithelial Na+ channels

Abstract: Hypoxia inhibits Na and lung fluid reabsorption, which contributes to the formation of pulmonary edema. We tested whether dexamethasone prevents hypoxia-induced inhibition of reabsorption by stimulation of alveolar Na transport. Fluid reabsorption, transport activity, and expression of Na transporters were measured in hypoxia-exposed rats and in primary alveolar type II (ATII) cells. Rats were treated with dexamethasone (DEX; 2 mg/kg) on 3 consecutive days and exposed to 10% O(2) on the 2nd and 3rd day of trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
64
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(71 citation statements)
references
References 35 publications
7
64
0
Order By: Relevance
“…We have shown that sodiumabsorbing epithelia have the capacity to produce H 2 S in concentrations that reflect the range of the observed inhibition of ENaC. H 2 S might, thus, contribute to hypoxic inhibition of sodium transport in pulmonary epithelial cells (35,47,65,77,82). 2) In low concentrations, H 2 S exerts anti-inflammatory, anti-oxidant, and vasoactive properties and is currently being evaluated as a potential therapeutic option in animal models of various lung diseases (15,49,81), including acute lung injury (ALI) (25-27, 29, 64).…”
Section: Perspectives and Significancementioning
confidence: 71%
“…We have shown that sodiumabsorbing epithelia have the capacity to produce H 2 S in concentrations that reflect the range of the observed inhibition of ENaC. H 2 S might, thus, contribute to hypoxic inhibition of sodium transport in pulmonary epithelial cells (35,47,65,77,82). 2) In low concentrations, H 2 S exerts anti-inflammatory, anti-oxidant, and vasoactive properties and is currently being evaluated as a potential therapeutic option in animal models of various lung diseases (15,49,81), including acute lung injury (ALI) (25-27, 29, 64).…”
Section: Perspectives and Significancementioning
confidence: 71%
“…Instead, O 2 alters expression of HO-1 and Glut1, genes that are minimally altered by steroids. Given these differences, the previously described prevention of hypoxiainduced ENaC inhibition by glucocorticoids in lung epithelia (25) probably represents a counterregulation of ENaC via a parallel pathway rather than prevention of the hypoxic effects (Fig. 1).…”
Section: Discussionmentioning
confidence: 87%
“…125,126 Hypoxia also has direct effects on expression of ENaC subunits and activity in rodent airway epithelial cells. 127,128 Further clinical correlations of these phenomena are warranted to ascertain their physiologic or pathophysiologic importance. A schematic working model of the regulation of ENaC by various signaling pathways is shown in Figure 2.…”
Section: Metabolic Depletion and Phmentioning
confidence: 99%